Suspensão de anti-retrovirais após o parto e a ocorrência de rebote da carga viral em mulheres infectadas pelo HIV - Ines Katerina Damasceno Cavallo (2008)
The benefits of potent antiretroviral therapy (ART) to decreaseHIV mother-to-child transmission during pregnancy are wellestablished. However, the safety of discontinuation of potent ART to themothers future is unknown. Considering that women who discontinueART at delivery may be at risk for additional increases in HIV-1 RNApostpartum, we aimed to evaluate changes in HIV-1 RNA and CD4 cellcounts levels six months after pregnancy and to compare these resultsbetween two groups: women who discontinued ART at delivery(prophylactic group) and those continuing ART after delivery(therapeutic group). This prospective, observational, study wasperformed from January 2003 to December 2007. Local Etichis ReviewBoard approval was obtained. A total of 112 women were included, 60receiving prophylatic ART and 52 receiving therapeutical medication.We evaluate viral load rebound in both groups and their related factors.In the prophylatic group 84.7% of the women had viral load reboundagainst only 15.3% of the therapeutic one (p=0.000). Forty twowomen with viral load rebound (80.8%) were HIV diagnosed duringpregnancy (actual or prior) against 57.5% of women without viralrebound (p=0.015). Among viral load rebound women, 84.9% had notbeen diagnosed with AIDS, in comparison to 58.8% of women with noviral rebound who had already been diagnosed with AIDS (p=0.000).Patients with viral load rebound had a significant decrease in their CD4cell counts six months after delivery, 30.4% of patients against only2.0% in no rebound group (p=0.000). The prior pregnancy rate wassignificant higher in the no rebound group (p=0.020), as well as thenumber of prenatal consultation (p=0.001). No viral rebound patientsstarted the prenatal care earlier than rebound group (p=0.012). Inmultivariate regression, viral load rebound during postpartum wassignificant related with the type of ART used (prophylactic ortherapeutic), the decrease in CD4 cell counts in postpartum, and thenumber of prenatal consultations. Our results suggest thatdiscontinuation of ART after delivery increase HIV-1 RNA postpartumassociated with CD4 cell counts decrease.